2006
DOI: 10.1016/j.immuni.2006.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Altered Peptide Ligands Induce Delayed CD8-T Cell Receptor Interaction—a Role for CD8 in Distinguishing Antigen Quality

Abstract: How T cells translate T cell receptor (TCR) recognition of almost identical pMHC ligands into distinct biological responses has remained enigmatic. Although differences in affinity or off rate are important, they offer at best an incomplete explanation. By using Förster resonance energy transfer (FRET), we have visualized the ligand-induced interaction between OT-I TCR and CD8. We found that both recruitment of TCR to the immunological synapse and the TCR-CD8 interaction induced by weak agonists (positive-sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
116
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(130 citation statements)
references
References 34 publications
14
116
0
Order By: Relevance
“…Note that in ref. 27 only the number of activated T cells was measured, but not actual phosphorylation levels, which turned out to be very sensitive to coreceptor-MHC interactions in later experiments from the same laboratory(28) (although still being above the activation threshold). These observations suggested that CD8 contributes to T-cell activation via an unknown mechanism unrelated to surface stabilization of pMHC (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that in ref. 27 only the number of activated T cells was measured, but not actual phosphorylation levels, which turned out to be very sensitive to coreceptor-MHC interactions in later experiments from the same laboratory(28) (although still being above the activation threshold). These observations suggested that CD8 contributes to T-cell activation via an unknown mechanism unrelated to surface stabilization of pMHC (29).…”
Section: Discussionmentioning
confidence: 99%
“…The simulated surface is divided into square chambers of the length L = 100 Å (0.01 μm), which implies that we simulate 100 × 100 chambers. The dimensions of the individual chamber are chosen to correspond to the range of attractive interactions between membrane-bound proteins (27). We ignore internal degrees of freedom in proteins, and proteins can react with each other provided that both are in the same chamber (i.e., they are within the range of interactions).…”
Section: Methodsmentioning
confidence: 99%
“…Because the polarized release reported by the Janeway group was only observed at low levels of TCR stimulation, we investigated the possibility that the absence of synaptic restriction in our live-cell imaging paradigm was due to strong signaling at the OT-I TCR. To control the level of antigenic stimulation, we pulsed astrocytes with increasing concentrations of the canonical OT-I epitope SIINFEKL and two altered peptide ligands, SIIG-FEKL and EIINFEKL, which have been demonstrated to mediate respectively intermediate and low signaling at the OT-I TCR (15). After washing, cocultures of astrocytes and OT-I T cells were incubated for 6 h, fixed, and immunolabeled for IFN-γ, LFA-1 and phosphorylated Stat1.…”
Section: T-cell Signaling To Nontarget Cells Is Independent Of Antigementioning
confidence: 99%
“…CTLs express both TCR and CD8, which may bind different sites on the same or different pMHCs (12,18,37). A given TCR is capable of binding different peptides complexed with MHC of the same allele with different kinetic rates and affinities, which can differentially trigger T cell activation (10,11).…”
Section: Isolation Of Mhc-cd8 Binding From the Trimolecular Tcr-mhc-cmentioning
confidence: 99%